IMPLEMENTASI PEMBANGUNAN DAERAH: STRATEGI MANAJEMEN SUNGAI "KALI SEMARANG" - Soesanto, Harry (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2005)
The stream of Semarang river starts from the southern part of Semarang, precisely from Kaligarang dam, then down to east until near Kariadi General Hospital and Flower market (defined as upper-stream) and passes behind Lawang Sewu building, Mayor Semarang Office, and Jalan Inspeksi in Thamrin (defined as middle-stream). To the north, goes to China town, Johar Market, Mberok Bridge and stream down to Java Sea (defined as lower-stream).Until 1970 s, Semarang River was remaining used by community for washing, bathing and rearing fish. Even reach to early 1980 s many home industry of tempe-tahu (a kinds of dish made by soyabeans which famous known as Javanese dish) utilized this river to wash the raw materials. However, all of those activities were dramatically gone due to the river is no longer sufficient to accommodate these purposes. Today, Kali Semarang is utilized by community for sewage, disposing garbage and drainage. The river body of Semarang River becoming shallow and narrower, then adversely due to the riverbank are utilized for illegal settlement and other purposes.Institutional analysis and co-management approach that introduced by ICLARM (now is known as Wolfish) and defined in Pomeroy and William (1994) and Kuperan et al (2003) were employed to analyze the situation of Semarang River. The study found that involvement of community only is not enough to manage the river of Semarang. The government is the most suitable one since has authority, resources, and funding if to be compared by the other components of stakeholder.